The Productivity of Vocational Schools: The Role of Efficiency, Fairness, Transparency, and Accountability of Financial Management - Agoestina Mappadang; Khusaini - (WIDYAKALA: JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2021)
In the last decade, vocational education quality is one of the productivity measurements. To measure productivity were internal and external efficiency, the quality of graduates, financial management, and effectivity. This study aims to examine and analyzed the effect of the principles of efficiency, fairness, transparency, and accountability in financial management on vocational school productivity simultaneously or partially. The sampling technique used was a census. Data collection methods using questionnaires. Data analysis methods using logistic regression analysis. The results of this study could be concluded that teachers' perceptions of school productivity were good, but they're still needs to be an improvement in school policies in keeping schools productive and even increasing. The results both partially and simultaneous were the application of the principle of transparency and accountability proven to contribute significantly to increasing school productivity. Whereas the principle of efficiency and fairness didn’t significantly contribute to increasing the productivity of vocational schools in Business and Management in Tangerang Municipality. While simultaneously, the application of the principles of efficiency, fairness, transparency, and accountability in school financial management contributed to creating school productivity. The implication of this research was useful for improving the quality and productivity of vocational schools in Tangerang Municipality.